2021
DOI: 10.1038/s41467-021-25227-w
|View full text |Cite
|
Sign up to set email alerts
|

The missing linker between SUN5 and PMFBP1 in sperm head-tail coupling apparatus

Abstract: The sperm head-to-tail coupling apparatus (HTCA) ensures sperm head-tail integrity while defective HTCA causes acephalic spermatozoa, rendering males infertile. Here, we show that CENTLEIN is indispensable for HTCA integrity and function, and that inactivation of CENTLEIN in mice leads to sperm decapitation and male sterility. We demonstrate that CENTLEIN directly interacts with both SUN5 and PMFBP1, two proteins localized in the HTCA and related with acephalic spermatozoa syndrome. We find that the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…This cellular location of BmPMFBP1 is consistent with observations of PMFBP1’s cytoplasmic location in the round spermatids in the mouse [ 27 ]. In mature spermatozoa, mammalian PMFBP1 is a component of the sperm head-to-tail coupling apparatus assembly formed with interacting proteins CENTILEIN and SUN5 [ 39 ], and so is specifically localized to the fossa region of the sperm nucleus during sperm head elongation and differentiation [ 27 ]. However, if BmPMFBP1 similarly interacts with other sperm proteins, our fusion protein assay would be unlikely to detect it.…”
Section: Resultsmentioning
confidence: 99%
“…This cellular location of BmPMFBP1 is consistent with observations of PMFBP1’s cytoplasmic location in the round spermatids in the mouse [ 27 ]. In mature spermatozoa, mammalian PMFBP1 is a component of the sperm head-to-tail coupling apparatus assembly formed with interacting proteins CENTILEIN and SUN5 [ 39 ], and so is specifically localized to the fossa region of the sperm nucleus during sperm head elongation and differentiation [ 27 ]. However, if BmPMFBP1 similarly interacts with other sperm proteins, our fusion protein assay would be unlikely to detect it.…”
Section: Resultsmentioning
confidence: 99%
“…CNTLN facilitates equal segregation of cytoplasmic contents between daughter cells by recruiting the endosomal sorting complex required for transport machinery at the midbody ( 49 ). During sperm production, CNTLN, cooperating with SUN5 and PMFBP1, participates in HTCA assembly and integration of sperm head to the tail ( 50 ). In our results, the higher mRNA level in LCs indicated that cell proliferation was more obvious in them.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to establish or maintain the connection between the head and tail can result in acephalic spermatozoa syndrome in patients, which presents with unstable connections between the sperm head and tail, including bent configurations and completely detached sperm heads, ultimately resulting in infertility (Baccetti et al, 1989, Chemes et al, 1987, Chemes et al, 1999, Perotti et al, 1981). Defects at the connection between the sperm head and tail have been linked to infertility across many other species, including bulls (Blom and Birch-Andersen, 1970), mice (Wang et al, 2022, Zhang et al, 2021), and Drosophila (Anderson et al, 2009, Kracklauer et al, 2010, Li et al, 2004, Sitaram et al, 2012, Texada et al, 2008).…”
Section: Introductionmentioning
confidence: 99%